An investigation into the deceleration mechanisms of a projectile travelling through a liquid and the influence of hydrodynamic-ram effect - Blythe, D.; Evans, R.; Oldershaw, S.; Vann, C.; Miller, David; Easton, L.; Roberts, Andrew (Straightline Publishing Limited, 2021)
If fragmentation or a projectile such as a bullet were to penetrate an aluminium fuel tank, kinetic energy is introduced to the fluid contained within that tank. In turn, kinetic energy is also imparted to the aluminium tank structure, causing structural damage. This research project focussed on designing and constructing a re-usable vessel for repeat firing of projectiles into a liquid and the investigation of the hydrodynamic ram effect. The vessel should enable the use of high-speed imaging to allow the measurement and analysis of deceleration of different projectiles at different velocities.